Influence Quality of Service, Taxpayer Knowledge and Taxpayer Awareness Towards Taxpayer Compliance - Helmi Faisal Kholagi; Nurul Hidayah (Transpublika Publisher, 2025)
This study examines the factors influencing tax compliance among small and medium-sized enterprises (MSMEs) in West Jakarta. The research analyzes three key factors: quality of tax services, taxpayer knowledge, and taxpayer awareness. Using a quantitative approach, primary data was collected through online questionnaires distributed via Google Forms to 135 MSME taxpayers in West Jakarta. The data was analyzed using the Partial Least Square (PLS) method. The findings reveal that both taxpayer knowledge and awareness have significant positive effects on tax compliance. Specifically, taxpayers with better understanding of tax payment procedures and those with higher awareness of their tax responsibilities demonstrate increased compliance levels. These results align with previous research that established positive relationships between taxpayer knowledge, awareness, and compliance. Notably, the study found that service quality has no significant impact on taxpayer compliance, suggesting that the level of tax services does not influence taxpayers' willingness to fulfill their obligations. These findings contribute to the understanding of tax compliance behavior among MSMEs and have implications for tax policy and administration.